IMPLEMENTASI PERATURAN PEMERINTAH NOMOR 62 TAHUN 2010 TENTANG PEMANFAATAN PULAU-PULAU KECIL TERLUAR DI PULAU BENGKALIS KABUPATEN BENGKALIS - suhendri, dedi; Harapan Tua R.F.S; Adianto (Moderat : Jurnal Ilmiah Ilmu Pemerintahan, 2023)
In the implementation of the policy on Utilization of Outermost Small Islands on Bengkalis Island, Bengkalis Regency, it has not been fully realized as described in Government Regulation Number 62 of 2010 concerning Utilization of Outermost Small Islands. The economic level and infrastructure facilities on the coast and small islands have differences compared to the main islands. Therefore, a social and economic resource strategy is needed to increase community participation and capacity. This study aims to describe the Implementation of Government Regulation Policy Number 62 of 2010 concerning the Utilization of the Outermost Small Islands on Bengkalis Island, Bengkalis Regency and identify the factors that hinder the Implementation of Government Regulation Policy Number 62 of 2010 concerning the Utilization of the Outermost Small Islands on Bengkalis Island, Bengkalis Regency. This study uses Grindle’s theory regarding the factors that influence Policy Implementation. The type of research used is descriptive research with a qualitative approach. The data collection method was carried out by interview, observation and documentation. The results of this study indicate that in the implementation of the policy of Government Regulation No. 62 of 2010 concerning the Utilization of the Outermost Small Islands in Bengkalis Island, Bengkalis Regency, what happened was the weakness of government management in mobilizing organizational resources that involved in utilization because there are many agencies in formulating programs and policies so that they tend to run independently. There is no institution that becomes the center of control or regime in power over the policy of managing the outermost small islands functionally and structurally.